FADtrack: development of vehicle tracking system using GPS / Muhammad Fadhli Mayati, Syafnidar Abdul Halim and Mohd Hafifi Mohd Supir - Mayati, Muhammad Fadhli; Abdul Halim, Syafnidar; Mohd Supir, Mohd Hafifi (College of Computing, Informatics, and Mathematics, 2024)
An increasing reliance on personal vehicle on our day to day live has made losing it a devastating event that have increasing chance to occur due to rampant crime rates. A vehicle can be lost due to a variety of incidents, including theft, unauthorised use, or misplacing. The problem raises the possibility that our vehicle will be lost and that there won't be any hint that it may be found again. This project objective to develop a vehicle tracking using GPS with out-of-range notification. This integrated system will enable real-time monitoring and tracking of assets within an area. By leveraging IoT connectivity, the system will provide accurate location information of assets through geofencing which using ESP 8266 and GPS module. Four experiments were conducted in this project, functionality testing (connectivity testing, GPS testing and alert triggering testing) and network performance testing. The result show that FADTrack system work better in open spaces, the system consistently achieves efficient alert notification with delays consistently under 30 seconds. The shorter delay times, such as 20 seconds at 80 meters in open areas. While building areas, where errors occur at longer distances (80 meters and 100 meters). The recommendation for future studies is to get a better GPS signal module to make this system can be useful anywhere even in the area around the obstruction.